Dynamic Strategies on Firm Production and Platform Advertisement in Crowdfunding considering Investor’s Perception - Ying Ji; Ju Wei; Zhong Wu; Shaojian Qu; Baojun Zhang (Discrete Dynamics in Nature and Society)
Taking investor’s perception into account, the optimal decisions about the product quality and platform advertisement are investigated in a dynamic model in the context of crowdfunding. Researches in the literature, however, usually set investor’s perception as a fixed value and rarely consider the important phenomenon that the online information has some influences on investor’s perception. Considering the effects of information about product quality and platform advertisement on the investor’s perception, a dynamic decision model is proposed. Firstly, investment desire and reference price of the investor are introduced in two dynamic settings to describe investor’s perception. Then, the optimal decisions about the product quality and platform advertisement are formulated under two circumstances: the sponsor and the platform make decisions independently and they cooperate as a system. Finally, the influences of reference price and cost-sharing ratio on the optimal results are compared and the data simulation experiment verifies the necessity of the study. Some new insights can be drawn for the operations management of the firm in crowdfunding as follows: (i) it is more profitable for the firm to cooperate with the platform when investors pay more attention to their reference price; (ii) it is optimal for the firm to share a larger proportion of platform cost when the profit-sharing ratio is low.